Focal glomerulosclerosis treated with heparin. Issue 6 (June 1989) - Lines, D R; Coleman, M; Gallus, A
Abstract : A boy with focal glomerulosclerosis as a result of nephrotic syndrome became unresponsive to corticosteroids and cyclophosphamide. He was given prolonged subcutaneous heparin with reduction in proteinuria, return of corticosteroid sensitivity, and no further deterioration (possibly improvement) in histological appearance. He remained completely well after five years.